Analisis Stuktur Sel dan Perkembangan Sel Limfosit B dan Sel Limfosit T Serta Mekanismenya - Ni’matullathifah Ni’matullathifah; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
B lymphocyte cells and T lymphocyte cells are two important types of cells in the human body's immune system. B Lymphocyte cells are responsible for producing antibodies that identify and help eliminate pathogens, such as bacteria and viruses. They also play a role in the adaptive immune response and can become memory cells, allowing the body to respond more quickly if exposed to the same pathogen in the future. T lymphocytes on the other hand, function in the recognition and destruction of cells infected by viruses as well as in regulating the immune response. T cells can be divided into several subtypes, including cytotoxic T cells, which directly destroy infected cells, and helper T cells, which help coordinate the immune response by secreting cytokines. These two types of cells work together to provide effective protection against infection and contribute to immunological memory, which is important for long-term immunity